Legal responsibility of hospital directors in doctor-patient medical disputes - Lisa Arttistika Pabidang; Nadir Nadir; Adriana Pakendek (Lentera Negeri, 2026)
The objectives of this study include: (1) analyzing the legal responsibilities of hospital directors in the resolution of medical disputes between doctors and patients; and (2) analyzing the resolution of medical disputes between doctors and patients that occur in hospitals. The type of research used in this study is normative legal research. The legal sources used are divided into several categories, namely primary, secondary, and tertiary legal sources. Legal analysis was conducted using the deductive method. The results showed that the legal liability framework for the Hospital Director based on the doctrine of vicarious liability in resolving medical disputes combines aspects of material law (who is responsible and on what basis) and formal/procedural law (how the dispute is resolved). Article 193 of Law No. 17 of 2023 concerning Health explains that the Hospital is responsible for the negligence of medical/health personnel working under its auspices. Hospital directors can be held directly accountable if proven negligent in managing the service system, supervision, facilities, and patient complaint resolution mechanisms, and can also bear indirect responsibility for the negligence of medical personnel or health human resources under their supervision through the principles of institutional responsibility and vicarious liability. However, this responsibility is not absolute, because the relationship between doctor and patient is essentially an obligation of effort or inspanning verbintenis, not an obligation of results, so that medical failure does not automatically constitute a basis for legal responsibility if the doctor has acted in accordance with professional standards, service standards, and applicable operational procedures.